Love arrives in pieces - St. Amant, Betsy (Zondervan, 2015)
"Former pageant queen Stella Varland doesn't trust beauty anymore after her divorce. Her appearance betrayed her and led to brokenness, so instead of being beautiful, now she tries to make beautiful things, but she always falls short ... If she doesn't get another job soon, she'll be stuck living with her parents. Contractor Chase Taylor is determined to live a life of no regrets after losing his fiancée. Now he lives life at full speed, striving to see how much he can accomplish. He knows if he slows down, he'll fall apart. So he returns home to Bayou Bend to renovate the town's old theater and is shocked to discover that the designer for the project is his old flame, Stella"--Amazon.com.